Segmentation in an Emerging Market A study into alternative segmentation variables - Mahanyele, Vuyelwa (My University, 2012)
It has been widely accepted that emerging markets will account for most of the world‘s economic growth in decades to come. Success in emerging markets will be a fundamental issue for most companies around the world. To remain practically relevant, marketing as a discipline has to adapt its practices to be relevant to the very different contexts found in emerging markets. The purpose of this study was to identify whether there are more appropriate segmentation variables and methodologies for emerging markets. The study was exploratory in nature and investigated whether culture, ethnicity and ubuntu, should be used as market segmentation variables, within an emerging market context. This was a qualitative study conducted through 13 in-depth interviews with leading marketers, researchers and strategists across diverse industries. A content analysis revealed key findings, which were captured in the form of themes. The conclusions of this report are that marketers believe micro-culture needs to be incorporated into marketing strategies when operating in emerging markets. However, it will be some time before these variables are successfully exploited because of their ambiguous nature, assumed costs and immeasurability. A proposed segmentation model has been developed as a guideline for multinational companies targeting the emerging market consumer
MBA thesis - WBS
Keywords: Market segmentation